Exponential Estimate for the Fundamental Matrix of a Linear Impulsive System - Petryshyn, R. I.; Sopronyuk, Т. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate the properties of oscillating sums and integrals dependent on parameters. These properties are used for the estimation of the normal fundamental matrix of a linear system with rapidly oscillating coefficients and pulse influence at fixed moments of time.